Case report of a combined oncocytoma and type 1 papillary renal cell carcinoma: a rare entity - Gaeta, R.; Tognetti, A.; Kauffmann, E.F.; Pollina, L.E (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
An extremely rare renal hybrid tumor composed of papillary renal cell carcinoma (PRCC) and renal oncocytoma (RO) within the same tumor is described. Only eight previous cases are documented in the literature. A 44-year-old man showed a 3.5 cm renal mass composed by areas with tubulo-papillary structures made up with small cells with scanty cytoplasm adjacent to polygonal cells forming solid sheet and tubules with abundant eosinophilic cytoplasm and uniform, round central nuclei without mitoses. Complete immunohistochemical panel suggested a diagnosis of type 1 PRCC combined with RO. Contrary to previous cases of hybrid renal tumors reported in the literature, no pseudocapsule divided the two histotypes of tumors. Our patient is the youngest among the previous reports being 44. Collision tumours have previously been described, although mixed renal tumours composed of oncocytoma and PRCC is extremely rare. There is no evidence to suggest a relationship between oncocytoma and papillary RCC since they originate from different cells and have different prognoses. Given the possibility of oncocytomas to harbour other tumours, we suggest careful examination of the samples to exclude the presence of an associated malignant neoplasm, which might have a significantly worse prognosis than oncocytoma. Differential diagnosis is needed, and immunohistochemical stains are of great help in distinguishing between the two histological components.